2020
DOI: 10.3390/antiox9020136
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Sulforaphane on Exercise-Induced Organ Damage via Inducing Antioxidant Defense Responses

Abstract: Regular exercise is beneficial to maintain a healthy lifestyle, but the beneficial effects are lost in the case of acute exhaustive exercise; this causes significant inflammation, oxidative stress along with organ damage. Recently, sulforaphane (SFN), an indirect antioxidant, has drawn special attention for its potential protective effect against inflammation and oxidative stress. However, no studies have been performed regarding acute exhaustive exercise-induced organ damage in association with SFN administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 77 publications
1
54
0
1
Order By: Relevance
“…Furthermore, creatinine phosphokinase (CPK) and lactate dehydrogenase (LDH) (two enzymatic markers to assess muscle damage) were significantly lower after SFN treatment compared to a placebo [ 81 ]. SFN treatment also protects exercise-induced liver damage, evidenced by reducing blood levels of enzymes such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST), via inducing antioxidant defense response through the transcriptional activation of the Nrf2/HO-1 signal transduction pathway [ 82 , 83 ]. Although exercise increases production of proinflammatory cytokines in the liver, kidney, and intestine [ 82 , 84 , 85 , 86 ], SFN induces phase 2 enzymes through Nrf2 activation in renal tissue to reduce renal oxidative insults [ 87 ].…”
Section: Effects Of Sfn On Exercise-induced Organ Damagementioning
confidence: 99%
“…Furthermore, creatinine phosphokinase (CPK) and lactate dehydrogenase (LDH) (two enzymatic markers to assess muscle damage) were significantly lower after SFN treatment compared to a placebo [ 81 ]. SFN treatment also protects exercise-induced liver damage, evidenced by reducing blood levels of enzymes such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST), via inducing antioxidant defense response through the transcriptional activation of the Nrf2/HO-1 signal transduction pathway [ 82 , 83 ]. Although exercise increases production of proinflammatory cytokines in the liver, kidney, and intestine [ 82 , 84 , 85 , 86 ], SFN induces phase 2 enzymes through Nrf2 activation in renal tissue to reduce renal oxidative insults [ 87 ].…”
Section: Effects Of Sfn On Exercise-induced Organ Damagementioning
confidence: 99%
“…They can interact with the oxidized species at both cellular and molecular levels by regulating gene expression, epigenetic controls, and protein and DNA repair. Previously it was reported that nutraceuticals have potential properties in immunity modulation, gene expression, and various signaling process regulation [ 153 , 154 , 155 , 156 , 157 , 158 ]. The nutraceuticals can be prepared from the foods available in the local market, for example, ginger, garlic, avocado, and onion, in the form of polyphenols, carotenoids, sulforaphane and other isothiocyanates, glucosinolate, phytosterol, etc.…”
Section: Roles Of Nutraceuticals As An Antioxidant In Reducing Oxidative Stressmentioning
confidence: 99%
“…This improvement may be due to antioxidant effect of sulforaphane as mentioned by Ruhee et al who reported the antioxidant defense system of sulforaphane through the Nrf2/HO-1 signaling pathway, on acute exhaustive exercise-induced inflammation. 27 Khaleel et al suggested that Nrf2 activation plays a critical role in mediating the protective effect of sulforaphane. 28 Sulforaphane (SFN) is an isothiocyanate abundant in cruciferous vegetables and, for a variety of diseases based on previous in vivo and in vitro studies, has been shown to be antioxidant via Nrf2 and can indirectly act as an antioxidant.…”
Section: C2 C3 Dmentioning
confidence: 99%